Akt/GSK3beta signaling during iron-induced neurotoxicity in HT22 hippocampal neurons - Uranga, Romina Maria (2010)
Akt and glycogen synthase kinase 3â (GSK3â) are key components of signaling pathways involved in synaptic plasticity and neuronal survival. The specific aims of this work were: i) to characterize an iron-induced neurodegeneration model and ii) to study the participation of Akt and GSK3â in the signaling events triggered during neuronal oxidative injury. For this purpose, a cell line of 2+ murine hippocampal neurons, HT22, was exposed to increasing Fe concentrations (25, 50, 100 and 200 ìM) for 24 h. Cell viability, morphology and lipid peroxidation were evaluated for determining the extent of neuronal injury. Cell viability, measured as MTT reduction, was significantly reduced in the presence of 50, 100 and 2+ 200 ìM Fe . HT22 cell morphology, evaluated by phase-contrast microscopy, showed evident morphological alterations including rounded cell body with a decreased number of cell projections. The decrease in MTT reduction strongly correlated with the changes in cellular morphology. Based on these data we defined that 24-h exposure to iron (25 and 50 ìM) caused a mild oxidative injury. Under these experimental conditions both Akt and GSK3â phosphorylation were increased. We conclude that iron-induced neurotoxicity activates Akt promoting GSK3â inhibition under mild oxidative injury in hippocampal neurons.